A mesh cladding-structured Sr-doped LaFeO3/Bi4O5Br2 photocatalyst: Integration of oxygen vacancies and Z-scheme heterojunction toward enhanced CO2 photoreduction. (April 2023) - Xie, Zhuohong; Seo, Woncheol; Ud Din, Syed Taj; Lee, Hankyu; Ma, Changchang; Yang, Woochul
Abstract: Solar-driven conversion of CO2 into beneficial chemical fuels using photocatalysts is a sustainable approach for obtaining renewable energy. However, the poor photoabsorption, low charge separation efficiency, and sluggish interfacial reaction due to a paucity of active sites limit the photocatalytic activity. Herein, a mesh cladding structure of Sr-doped LaFeO3 /Bi4 O5 Br2 (Sr-LFO/BOB) Z-scheme heterojunction with abundant surface oxygen vacancies (OVs) is developed to improve the CO2 photoreduction. Sr doping in LFO introduce OVs, which captures more photoinduced electrons contributing to the surface adsorption of CO2 molecules and narrows the LFO band gap extending the light absorption range to the whole visible spectrum. Particularly, the unique mesh cladding heterostructure composed of Sr-LFO particles wrapped with BOB nanowires provides ample Z-scheme charge-transfer pathways at the Sr-LFO/BOB and sufficiently exposes Sr-LFO surface for CO2 adsorption. Benefiting from the OVs and design of Z-scheme, the optimized photocatalyst (0.05Sr-LFO/BOB(2)) with appropriate Sr doping (5%) and BOB content demonstrates a considerable CH4 generation of 10.14 μmol g −1, which is approximately 48.3-fold higher than that of the pristine LFO. This study provides an insight into the design and fabrication of high-performance perovskite oxide-based photocatalysts by constructing a Z-scheme heterojunction with abundant active sites for CO2 photoreduction. Graphical abstract: Image 1 Highlights: Incorporating Sr to adjust light absorption capacity and oxygen vacancies of LaFeO3 . Successful synthesis of Sr-doped LaFeO3 /Bi4 O5 Br2 mesh cladding structure. Mech cladding structure allowed CO2 adsorption on ample active surface of LaFeO3 . Network-like Bi4 O5 Br2 enclosing Sr–LaFeO3 provides ample electron transfer pathways. A novel LaFeO3 /Bi4 O5 Br2 Z-scheme heterojunction has efficient CO2 photoreduction activity.